Dew as a Service for Intermittently Connected Internet of Drone Things - Mukherjee, Amartya; De, Debashis; Dey, Nilanjan; González Crespo, Rubén; Herbert Song, Houbing (Dew Computing, 2024)
With the recent advancement of the cloud, edge, and fog computing methodology data processing and buffering become more crucial tasks. This is even more critical for real-time applications like the Internet of Drone Things. The traditional edge-fog-cloud methodology highly relays on strong Internet connectivity. In case of a mission-critical situation like UAV-based surveillance, aerial reconnaissance mission, or disaster management the network connectivity becomes extremely intermittent. As a result of that, there is a high chance of packet loss. To avoid this situation, the Dew computing methodology can be considered. In this system, the state-of-the-art Dew-enabled nodes will be taken into account as a part of the Internet of Drone Things structure to ensure Dew as a service phenomenon. This chapter primarily investigates the different components of the methodology of Dew as a Service (DewaaS). Secondly, the impact of Dew as a service intermittently connected IoDT and the technical challenges. Finally, the possible use cases of DewaaS for mission-critical Drone applications.
Keywords: drone; Dew; Internet; Scopus